Analisis Tingkat Pemahaman Terhadap Generasi Z Mengenai Pasar Uang Dan Pasar Modal Di Indonesia - Dwiki Wardana Syah; Cindy Er Nisa; Mutia Zahra Lubis; Fauzi Arkhan Sembiring; Muhammad Ikhsan Harahap (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This article aims to analyze the level of understanding among Generation Z in Medan, Indonesia, regarding the money market and capital market. The study employs a survey method with questionnaires distributed to 100 respondents aged 18-25 in Medan. The collected data are descriptively analyzed to depict the respondents' knowledge and understanding of the basic concepts, instruments, and operational mechanisms of the money market and capital market. The research findings indicate that although most of Generation Z in Medan are aware of the existence of financial markets, their understanding of the operational details and functions of the money market and capital market remains relatively low. Education and access to information are identified as primary determinants influencing this understanding level. These findings indicate the need for enhanced financial literacy through more intensive and targeted educational programs for this age group in Medan.